Direct and Indirect Experiential Effects in an Updating Model of Deterrence: A Research Note. (February 2017) - Wilson, Theodore; Paternoster, Ray; Loughran, Thomas
Objectives: Sanction risk perceptions are a central element of deterrence theory, but the process by which an offender's direct and indirect criminal experiences contribute to future risk perceptions has been understudied. This note seeks to address this domain through an extension of updating model of Anwar and Loughran to account for two distinct information signals obtained by an offender through (1) their personal criminal experiences and (2) the criminal experiences of their family members. Further, this model is extended to assess for any differential updating according to the presence of low impulse control. Methods: Data for this analysis were obtained from the Pathways to Desistance study. Random effects models were employed to model the updating process directly. Results: Having criminal family members who did not get arrested during the current period had the most criminogenic effect upon one's personal perception of sanction risk, but simply having family members commit crime, regardless of sanction status, appears to be criminogenic. Those with low impulse control place greater weight upon their personal information than vicarious information obtained from their family members. Conclusions: These findings offer some insight into a mechanism that may underlay the delinquent peer effect and warrants future inquiry.